Batangas City Public Library a study on their response to the social needs of its community - Lacsamana, Alistair Troy B. (1995)
The basic elements of public library service include the communication of ideas, knowledge, information and experience; liaising with the cultural framework, responding to social needs: information, education and recreation. And among all libraries, it is the public library which must meet the challenge of poverty and deprivation. It is the requirement to respond to social needs that distinguishes from other types of library. According to David Liddle, the real business of libraries is community development, improving the quality of individual lives and encouraging the development of their communities. The key mission, therefore, is one of service and responsibility. Social responsibility is what all have towards the major public issues facing society (Martin, 1989).The study sought to answer the following questions:1. Is the Batangas City Public Library aware of the social needs of their communities? What are these?2. What is the level of understanding of the librarians on these social needs?3. How do the librarians respond to these needs?4. What are the barriers in meeting these needs?